A complex intervention to reduce hospital admissions for people living with dementia in shared-housing arrangements in Germany: results of the multicenter, cluster-randomized controlled DemWG-study - Misonow, Julia; Wolf-Ostermann, Karin; Altona, Janissa; Schmidt, Annika; Stiefler, Susanne; Guenay, Serhat; Kratzer, André; Keck, Antonia; Donath, Carolin; Grässel, Elmar (BMC Medicine, 2025)
Background: People living with dementia (PlwD) have a 1.4 times higher risk of hospitalization than people living without dementia. Hospital admissions lead to negative consequences for PlwD and people living with mild cognitive impairment (PlwMCI). Housing models such as shared-housing arrangements (SHAs), which are predominantly used by PlwD, enable care-dependent people to experience daily life as ordinary as possible. However, studies are needed to show how complex non-pharmacological interventions affect hospital admissions, especially in the SHAs setting. Methods: The longitudinal, multicenter, cluster-randomized, controlled, and prospective mixed methods study from April 1, 2019, to December 31, 2022, was part of the German DemWG study and included a waitlist control group design. The multicomponent complex intervention consisted of (a) education of nursing staff in the SHAs—at the beginning of the study, (b) digital education of general practitioners—at the beginning of the study, and (c) the multimodal, psychosocial group intervention MAKS-mk + —structured application of MAKS-mk + between t0 (baseline) and t1 (after 6 months). Longitudinal data were collected at three survey times t0-t2 (t2 at another 6 months follow-up). The primary outcome parameter—hospital admission—was assessed using the nursing documentation. Poisson-models with hierarchical random effects were used for statistical analysis. Results: Nationwide, 97 SHAs with 341 residents participated at t0. Within the longitudinal observation period (12 months, t0-t2), data from 236 participants at t1 and 168 participants at t2 with mild cognitive impairment or mild to moderate dementia were evaluated. In the intention-to-treat sample, the adjusted Poisson-model showed that participants in the intervention group (IG, n = 201) had a significantly lower number of hospital admissions at t1 than participants in the control group (CG, n = 140) (p-value = 0.048; CI = 0.22; 0.99). Beyond t1—“open phase” of the study, no further statistically significant long-term effects of the IG could be identified (p-value ≤ 0.498; CI = 0.25; 1.98). Conclusions: The complex intervention significantly reduced the number of hospital admissions for PlwD and PlwMCI in the “structured phase” of DemWG. This leads to significant improvements in the nursing care and living situation for PlwD and PlwMCI. Since the intervention has been proven to have positive effects and can be easily integrated into SHAs, regular and nationwide integration into everyday care should be given greater consideration. Trial registration: ISRCTN89825211 (Registered prospectively, 16 July 2019).
CRIS-Team Scopus Importer:2025-05-16
Keywords: Cognitive dysfunction; Complex intervention; Dementia; Hospitalization; Housing for the elderly; Psychosocial intervention; Randomized controlled trial; Shared-housing arrangements

Agitation and aggression in people living with dementia and mild cognitive impairment in shared-housing arrangements – validation of a German version of the Cohen-Mansfield Agitation Inventory-Short Form (CMAI-SF) - Kratzer, André; Scheel-Barteit, Jennifer; Altona, Janissa; Wolf-Ostermann, Karin; Grässel, Elmar; Donath, Carolin (Health and Quality of Life Outcomes, 2023)
Background: The Cohen-Mansfield Agitation Inventory-Short Form (CMAI-SF) is a 14-item scale for assessing agitation and aggression, derived from the original 29-item CMAI, and completed by a proxy. Because the CMAI-SF has not yet been validated in German language, the aim of this study is to explore its construct validity. Methods: Baseline data from a cluster-randomized trial to evaluate a non-pharmacological complex intervention for people living with dementia (PlwD) and mild cognitive impairment (MCI) were analyzed. The study sample consisted of 97 shared-housing arrangements (SHAs) in Germany, comprising N = 341 residents with mild to severe dementia and MCI. Trained nursing staff collected data by proxy-rating the CMAI-SF, Neuropsychiatric Inventory-Nursing Home Version (NPI-NH), and QUALIDEM. They also conducted the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA). Results: In an exploratory factor analysis, three factors emerged: “aggressive behavior”, “verbally agitated behavior”, and “physically non-aggressive behavior”. The CMAI-SF total score showed good internal consistency (α =.85), and the factors themselves showed adequate internal consistency (α =.75/.76/.73). The CMAI-SF showed convergent validity with the NPI-NH agitation item (r =.66) and the NPI-NH “agitation & restless behavior” factor (r =.82). Discriminant validity was confirmed by a low (r =.28) correlation with the NPI-NH apathy item. Quality of life decreased significantly with agitation, as the CMAI-SF showed a moderate negative correlation with the QUALIDEM total score (r = -.35). Conclusions: The 14-item CMAI-SF is a time-efficient, reliable, and valid assessment instrument. Three factors emerged that were similar to those already found in nursing home samples for the original CMAI and the CMAI-SF and in day care samples for the CMAI-SF. The findings provide preliminary evidence that the CMAI-SF can be used instead of the CMAI to reduce time, costs, and burden in future trials. Trial registration: The DemWG study from which data were used to draft this manuscript was prospectively registered on 16 July 2019 at ISRCTN registry (ISRCTN89825211).
CRIS-Team Scopus Importer:2023-06-09
Keywords: Aggression; Agitation; CMAI; CMAI-SF; Cohen-Mansfield Agitation Inventory; Dementia; Mild cognitive impairment; Reliability; Shared-housing arrangements; Validity

Bouldering psychotherapy is effective in enhancing perceived self-efficacy in people with depression: results from a multicenter randomized controlled trial - Kratzer, André; Luttenberger, Katharina; Karg-Hefner, Nina; Weiss, Maren; Dorscht, Lisa (BMC Psychology, 2021)
Background: Recent studies have suggested that therapeutic climbing/bouldering may have positive effects on perceived self-efficacy. Nevertheless, there is still an urgent need for high-quality studies, as many existing studies have suffered from methodological problems. Therefore, the current work was aimed at investigating the effect of a manualized bouldering psychotherapy (BPT) on perceived self-efficacy in people with depression, compared with a home-based physical exercise program (EP) and state-of-the-art cognitive behavioral group therapy (CBT). Methods: In a prospective, multicenter, randomized controlled trial, 233 people with depression were randomly assigned to one group (BPT, EP, or CBT). Perceived self-efficacy was assessed at baseline (t0) and directly after the 10-week intervention period (t1) with the GSE. In addition, depression was assessed with the PHQ-9 and the MADRS. We computed t tests, analyses of variance (ANOVAs), confounder-adjusted hierarchical regression analyses, mediation analyses, and several sensitivity analyses. Results: BPT participants showed a significantly larger increase in perceived self-efficacy on the GSE compared with the EP (an increase of 3.04 vs. 1.26 points, p =.016, Cohen’s d = 0.39). In the confounder-adjusted hierarchical multiple regression analysis, group allocation (BPT vs. EP) was found to be the only significant predictor of the postintervention GSE score (β =.16, p =.014) besides the baseline GSE score (β =.69, p <.001). No differences were found between BPT and CBT participants regarding the effect on perceived self-efficacy. Only in the CBT group, the relationship between depression at baseline and postintervention was partially mediated (23%) by perceived self-efficacy. Conclusions: Participation in the manualized BPT in a group setting leads to a clinically relevant enhancement of perceived self-efficacy in people with depression. This effect is superior to that of physical exercise alone. The results provide also initial indications that BPT is comparable to CBT in enhancing perceived self-efficacy, suggesting a strong case for a broader use of BPT as a supplement to existing health services. Future studies should focus on the modes of action of BPT and its effect on perceived self-efficacy in people with other mental or physical disorders. Trial registration ISRCTN12457760, registered partly retrospectively, 26 July 2017.
Created from Fastlane, Scopus look-up
Keywords: Bouldering; Depression; Physical Exercise; Psychotherapy; Self Efficacy; Therapeutic climbing

DemWG - Improving the Care of People with Dementia in outpatient assisted Living Communities - Donath, Carolin; Kratzer, André; Scheel, Jennifer Felicia; Schmidt, A.; Friedrich, A-C; Stiefler, S.; Wolf-Ostermann, K.; Grässel, Elmar (GESUNDHEITSWESEN, 2021)
CRIS-Team WoS Importer:2022-05-20

DemWG - Reduction of the Risk for Hospital Admissions in People with Dementia in community-managed Residential Communities - Wolf-Ostermann, K.; Ratz, K.; Grässel, Elmar; Kratzer, André (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2019)
CRIS-Team WoS Importer:2019-09-06

Einflussfaktoren auf die Pflegebelastung der Angehörigen von Menschen mit Demenz: der Bayerische Demenz Survey (BayDem) - Dietzel, Nikolas; Karrer, Linda; Wolff, Franziska; Kratzer, André; Hess, Manuela; Grässel, Elmar; Kolominsky-Rabas, Peter (Gesundheitswesen, 2020)
Background Dementia is an age-specific disease with increasing care needs over the course of the disease. Care is predominantly conducted by caregivers. Caregiver burden is a core criterion for the evaluation of the care situation. The aims of this examination are to identify predictors of caregiver burden and to analyze the course of the caregiver burden over a 12 months period. Methods The Bavarian Dementia Survey (BayDem) is a supra-regional, longitudinal study carried out at 3 different sites in Bavaria, Germany. Participants were people with dementia (pwd) as defined by ICD-10 and their informal caregivers. Data was collected by standardized face-to-face interviews in cooperation with local actors. For statistical analysis, a multiple regression as well as a mixed ANOVA (Analysis of Variance) and repeated measures ANOVAs were used. Results In this analysis, 295 pwd and 276 caregivers were studied. Key factors influencing caregiver burden were gender of the pwd, behavioral and psychological symptoms and a decline of everyday functioning of the pwd as well as gender of the informal caregivers, their relation to the pwd and if they live at the same household as the pwd. Analysis showed a significant main effect of time over the course of the caregiver burden. Conclusion A permanent high caregiver burden can cause health problems for the caregivers. However, caregivers can be supported according to the specific factors of the caregiver burden. One approach in order to support caregivers could be a combination of pharmacological and non-pharmacological interventions for the treatment of disease-specific symptoms and an empowerment as well as the provision of support services for the caregivers. Furthermore, tailored services for specific target groups can be meaningful.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Burden Scale for Family Caregivers (BSFC-s); caregiver burden; course; dementia; informal caregivers; predictors

Mild behavioral impairment in people with mild cognitive impairment: Are the two conditions related? - Scheuermann, Julia-Sophia; Grässel, Elmar; Kratzer, André; Scheerbaum, Petra (Journal of Alzheimer's Disease, 2024)
BACKGROUND: Mild cognitive impairment (MCI) and mild behavioral impairment (MBI) are both considered potential prodromal stages of dementia, especially Alzheimer's disease. Previous literature has lacked specific information about MBI in individuals with MCI and associations of several aspects of both, MBI and MCI. OBJECTIVE: Our aim was to investigate whether associations exist between aspects of MBI and aspects of cognitive performance in certain dimensions of the Montreal Cognitive Assessment (MoCA). METHODS: We used baseline data from the double-blind randomized controlled intervention MCI-CCT-study. Current cognitive performance of individuals with MCI was measured with the MoCA. MBI was assessed with the MBI Shortscale (MBI short), which was administered through a self-report interview. Associations were assessed with Pearson correlations. Sensitivity analyses were conducted for gender and cognition. Group differences were examined with independent samples t-tests or Welch test. Significant correlations were considered in binary logistic regressions under control of covariates. RESULTS: There was no significant correlation between the current MoCA and MBI short scores in the total sample or in the gender-related analysis. Using dichotomized cognitive performance, significant correlations between MCI and MBI were revealed for individuals with lower MoCA scores. On the task level, several significant associations were identified between MoCA dimensions and MBI dimensions in the total sample and in the sensitivity analyses, also under control of covariates. CONCLUSIONS: Our findings support the hypothesis that with increasing cognitive decline, the association between MCI and MBI becomes stronger. Furthermore, a certain cut-off on the MoCA must be reached to identify a correlation.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Alzheimer's disease; behavioral and psychological symptoms of dementia; cognition; mild behavioral impairment; mild cognitive impairment; Montreal Cognitive Assessment

Non-pharmacological, psychosocial MAKS-s intervention for people with severe dementia in nursing homes: results of a cluster-randomised trial - Kratzer, André; Diehl, Kristina; Gefeller, Olaf; Meyer, Sebastian; Grässel, Elmar (BMC Geriatrics, 2022)
Background: Severe dementia is one of the most challenging conditions when caring for people in nursing homes. A manualised non-pharmacological, psychosocial group intervention especially adapted to the needs of people with severe dementia (PWSDs) is currently still lacking. To close this gap, we adapted the evidence-based multicomponent non-pharmacological MAKS intervention (Motor stimulation, ADL stimulation, Cognitive [german: Kognitive] stimulation, and Social functioning in a group setting) to the special needs of PWSDs called the MAKS-s intervention, where the s stands for severe dementia. Methods: In a prospective, multicentre, cluster-randomised trial with a waitlist control group design, 26 nursing homes comprising 152 PWSDs were randomly assigned to either the MAKS-s intervention group (IG) or control group (CG) – 121 PWSDs were still alive after the 6-month intervention period (t6) and included in the intention-to-treat (ITT) sample. The two primary outcomes, behavioural and psychological symptoms (BPSDs, measured with NPI-NH) and quality of life (QoL, measured with QUALIDEM), and the secondary outcome, activities of daily living (ADLs, measured with ADCS-ADL-sev), were assessed at baseline (t0) and at t6. Mixed ANOVAs were computed to investigate possible effects of the MAKS-s intervention on the outcomes. Results: In the ITT sample, BPSDs and QoL did not change significantly over time, and group assignment did not affect them, although the IG participants had significantly better overall QoL than the CG participants. ADLs decreased significantly over time, but group assignment did not affect them. Analyses in the per protocol (PP) sample showed comparable results, with the exception that the IG participants showed a significantly greater increase in BPSDs than the CG participants did. Discussion: Under the situational conditions of the Covid-19 pandemic, no beneficial effects of the MAKS-s intervention on BPSDs, QoL, or ADLs were observed. This finding also means that under ‘normal circumstances’ (i.e., if there had been no pandemic), we could not make any statements about the effect or non-effect of MAKS-s. In order to be able to address the hypotheses formulated here, the study will have to be repeated incorporating helpful experiences of the present study. Trial registration: https://doi.org/10.1186/ISRCTN15722923 (Registered prospectively, 07. August 2019).
Created from Fastlane, Scopus look-up
Keywords: Behavioural and psychological symptoms of dementia; Nursing home; Psychosocial intervention; Quality of life; RCT; Severe dementia

Predictors of falls and hospital admissions in people with cognitive impairment in day-care: role of multimorbidity, polypharmacy, and potentially inappropriate medication - Scheel, Jennifer; Luttenberger, Katharina; Grässel, Elmar; Kratzer, André; Donath, Carolin (BMC Geriatrics, 2022)
Background Multimorbidity, polypharmacy, and potentially inappropriate medication (PIM) pose challenges for the care of people with cognitive impairment. The aim of the present study is to explore whether multimorbidity, polypharmacy, and PIM predict falls and hospital admissions in a sample of people with cognitive impairment in day-care centers in Germany. Methods We used data from the German day-care study (multicenter longitudinal study, n = 433). Multimorbidity was defined as >= 2 chronic diseases. Polypharmacy was defined as prescriptions to >= 5 drugs. Potentially inappropriate medication was defined as scoring on the PRISCUS list. Binary logistic regression analyses were computed to determine whether multimorbidity, polypharmacy, and potentially inappropriate medication at t0 predicted falls and hospital admissions as outcomes at t1 (six months later). Results The rate of multimorbidity and polypharmacy was 87.8% and 60.3%, respectively. 15.9% of the people with cognitive impairment received PIM / PRISCUS-listed drugs, 43.6% ACB-listed drugs, and 52.7% CNS depressant drugs. Falls and hospital admissions during follow-up were prevalent in 19.4% and 24.7% of the people with cognitive impairment. Both were significantly predicted by the total number of drugs (falls: OR = 1.152, p = 0.001, overall model: p < 0.001; hospital admissions: OR = 1.103, p = 0.020, overall model: p = 0.001), even if regression analyses were controlled for the number of comorbidities. Conclusions Polypharmacy and potentially inappropriate medication are highly prevalent in people with cognitive impairment in German day-care centers. The number of drugs and appropriateness of medication seem to be crucial for the risk of falls and hospital admissions. Polypharmacy and PIM should be critically reviewed by healthcare providers and avoided as much as and whenever possible.
CRIS-Team WoS Importer:2022-08-26

Psychopharmakologische Behandlung von Menschen mit schwerer Demenz - Diehl, Kristina; Kratzer, André; Donath, Carolin; Maas, Renke; Fromm, Martin; Kornhuber, Johannes; Grässel, Elmar (Deutsches Ärzteblatt international, 2022)
CRIS-Team Scopus Importer:2022-11-25

RISK REDUCTION OF HOSPITAL ADMISSIONS FOR PEOPLE WITH DEMENTIA IN SHARED-HOUSING ARRANGEMENTS: THE DEMWG STUDY - Wolf-Ostermann, Karin; Stiefler, Susanne; Schmidt, Annika; Friedrich, Anna-Carina; Grässel, Elmar; Donath, Carolin; Scheel, Jennifer; Kratzer, André (INNOVATION IN AGING, 2022)
CRIS-Team WoS Importer:2023-03-10

SinoMAKS-protocol of a randomised controlled trial to evaluate the Chinese version of the non-pharmacological, multimodal MAKS intervention for people with mild to moderate dementia in Chinese nursing homes - Scheuermann, Julia-Sophia; Scheerbaum, Petra; Liu, Yu; Ding, Yaping; Lu, Jianwen; Zhong, Ming; Su, Jian; Gefeller, Olaf; Grässel, Elmar; Kratzer, André (BMJ Open, 2025)
INTRODUCTION: The prevalence of dementia is increasing, both worldwide and in China. This disease is associated with numerous restrictions for those affected but also for caregivers and society. Due to the limited effectiveness of pharmacological interventions, more research on non-pharmacological interventions is needed. For the non-pharmacological multimodal MAKS (M: motor training, A: activities of daily living training, K: cognitive training, S: social-communicative setting) intervention, positive effects on cognition, activities of daily living, and the occurrence of behavioural and psychological symptoms of dementia were identified in two randomised controlled trials in different settings in Germany. Thus, the German MAKS intervention was culturally adapted for China and will now be tested for its efficacy in Chinese nursing homes in a randomised controlled trial. METHODS AND ANALYSIS: Participants will be residents of Chinese nursing homes in Shenyang, Nanjing and Dalian, fulfilling the ICD-10 criteria for Alzheimer's dementia, the psychometric criteria for mild to moderate dementia (MMSE 10-23) and none of the exclusion criteria. With n=200, effects with an effect size of Cohen's d=0.45 and a power of 1-β = 0.80 can be detected. Screening and data collection at baseline, t6 and t12 will be conducted via face-to-face contact by proxy raters in the nursing homes (i.e., trained nursing staff not involved in the intervention) and master students as external testers for the performance tests on cognition and activities of daily living. Participants will be randomly allocated to the intervention or control group. SinoMAKS (i.e., the Chinese version of the MAKS intervention) will be conducted at least three times a week for six months by trained MAKS therapists. The control group will receive care as usual for 12 months after baseline. Thus, the treatment phase is six months with follow-ups after six and 12 months after baseline. In the open phase, from t6 to t12, the nursing homes are free to offer SinoMAKS to the intervention group residents. In line with international guidelines, the primary population for analysis is the intention-to-treat sample. Global cognition (measured with the Addenbrooke's Cognitive Examination-III) is the primary outcome. The hypotheses will be analysed using multiple linear regression with the outcome variables as dependent variables. ETHICS AND DISSEMINATION: All procedures were approved by the Ethics Committee of the Medical Faculty of the Friedrich-Alexander-Universität Erlangen-Nürnberg (Ref. 24-162-B) and the Ethics Committee of the China Medical University (Ref. [2024]181). Written informed consent will be obtained from all participants or-if applicable-their legal representatives. Results will be published in peer-reviewed scientific journals and conference presentations. TRIAL REGISTRATION NUMBER: ISRCTN10262531.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Clinical Protocols; Cognition; Dementia; Nursing Homes; Randomized Controlled Trial

Symptombelastung, Inanspruchnahme des Gesundheitssystems und Todesumstände von Menschen mit Demenz in der letzten Lebensphase: der Bayerische Demenz Survey (BayDem) - Kratzer, André; Karrer, Linda; Dietzel, Nikolas; Wolff, Franziska; Hess, Manuela; Kolominsky-Rabas, Peter; Grässel, Elmar (Gesundheitswesen, 2020)
Background Dementia is usually a life-limiting disease. However, evidence-based guidelines for palliative care for people with dementia (PwD) are currently lacking. One reason for this is the dearth of reliable empirical data on PwD at the end of life. The aim of this study is to describe the symptom burden, causes of death, places of death and the use of various health services for PwD at the end of life. Methods The Bavarian Dementia Survey (BayDem) was a multi-center, longitudinal study at 3 different sites in Bavaria, Germany (Dachau, Kronach, Erlangen). Participants were PwD defined by ICD-10 and their informal caregivers. Data were collected in standardized face-to-face interviews in cooperation with local actors. In order to obtain comparable groups, deceased and non-deceased PwD were matched using 1:1 propensity score matching. For the statistical analyses, McNemar tests as well as paired t-tests were used. Results In this analysis, 58 deceased and 58 non-deceased PwD were studied (n=116). In most cases, PwD died at home (36.2%), in hospital (25.9%) or in a nursing home (19.0%), but no one in palliative care. The most common causes of death were respiratory (13.8%) and cardiovascular complications (12.1%) as well as stroke (12.1%). PwD at the end of life showed more pronounced physical comorbidities than the other PwD (Charlson-Index: M=2.75 vs. M=1.80; p=0.030, Cohen's d=0.425) and were therefore admitted to hospital (46.6 vs. 12.1%, p<0.001, OR=6.250) or emergency departments (22.4 vs. 3.4%, p=0.007, OR=6.500) more frequently. Behavioral and psychological symptoms were very pronounced (NPI Score: M=31.67 vs. M=24.77, p=0.118, Cohen's d=0.303). Nevertheless, the utilization of outpatient health services was low. Conclusion The results underline the need to develop evidence-based guidelines to provide palliative care specifically adapted to the needs of PwD at the end of life. In this context, the high incidence of behavioral and psychological symptoms should be taken into account, as should the high incidence of physical comorbidities. Considering the frequent hospital admissions, special attention should also be paid to the development of recommendations for the inpatient sector (acute hospital and palliative care unit).
CRIS-Team Scopus Importer:2020-02-04
Keywords: Death; Dementia; End of life; Palliative care; Symtom burden; Utilization

The DemWG study: reducing the risk of hospitalisation through a complex intervention for people with dementia and mild cognitive impairment (MCI) in German shared-housing arrangements: study protocol of a prospective, mixed-methods, multicentre, cluster-randomised controlled trial - Kratzer, André; Scheel, Jennifer; Wolf-Ostermann, Karin; Schmidt, Annika; Ratz, Katrin; Donath, Carolin; Grässel, Elmar (BMJ Open, 2020)
INTRODUCTION: Shared-housing arrangements (SHAs) are small, home-like care environments in Germany. Residents are predominantly people with dementia. The risk for all-cause hospitalisation is consistently higher for people with dementia compared with people without dementia and there is currently no evidence-based intervention to reduce the risk of hospitalisation. Thus, the DemWG study investigates whether a complex intervention is effective in reducing hospitalisation (primary outcome), behavioural and psychological symptoms of dementia and falls and for stabilising cognitive functioning and quality of life in people with dementia and mild cognitive impairment (MCI) in German SHAs. METHODS AND ANALYSIS: Based on the UK Medical Research Council framework 'Developing and evaluating complex interventions', a prospective, mixed-methods, multicentre, cluster-randomised controlled trial combining primary and secondary data analyses as well as quantitative and qualitative research methods is being conducted. The intervention consists of three parts: (A) education of nursing staff in SHAs; (B) awareness raising and continuing medical education (CME) of general practitioners; (C) multicomponent non-pharmacological group intervention MAKS-mk+ ('m'=motor training; 'k'=cognitive training; '+'=fall prevention) for people with dementia and MCI. Randomisation is stratified by the German federal states and type of setting (rural vs urban). Neither the trained professionals nor the participants are blinded. Data are collected at baseline and after 6, 12 and 18 months with standardised instruments. Quantitative data will be analysed by multivariate analyses according to the general linear model, qualitative data using qualitative content analysis. Recruitment is still ongoing until 31 December 2020. ETHICS AND DISSEMINATION: All procedures were approved by the Ethics Committee of the University of Bremen (Ref. 2019-18-06-3). Informed consent will be obtained before enrolment of participants. Due to findings of previous randomised controlled trials, serious adverse events are not expected. Results will be disseminated in peer-reviewed journal publications and conference presentations. TRIAL REGISTRATION NUMBER: ISRCTN89825211.
CRIS-Team Scopus Importer:2020-12-11
Keywords: delirium & cognitive disorders; dementia; geriatric medicine

The MAKS-s study: multicomponent non-pharmacological intervention for people with severe dementia in inpatient care – study protocol of a randomised controlled trial - Diehl, Kristina; Kratzer, André; Grässel, Elmar (BMC Geriatrics, 2020)
Background: Nursing homes accommodate a large number of people with severe dementia. More than 80% of residents with dementia suffer from behavioural and psychological symptoms, that can have consequences on the perceived burden of the formal caregivers. Internationally, the number of studies on non-pharmacological interventions for people with severe dementia is very small. One way to reduce these symptoms is to meet the needs of people with severe dementia. The non-pharmacological group intervention MAKS-s, which we will investigate in this study, is intended to reduce the behavioural and psychological symptoms and to improve the quality of life of such people. Additionally, we will investigate the effects on the burden carried by formal caregivers. Methods: With the present study, we will investigate the effectiveness of a multicomponent non-pharmacological intervention for people with severe dementia living in nursing homes (primary target group). A power analysis indicated that 144 dementia participants should initially be included. In addition, a secondary target group (nursing home staff) will be examined with respect to their dementia-related stress experiences. The study will be conducted as a cluster randomised controlled trail in Germany with a 6-month intervention phase. The nursing homes in the waitlist control group will provide “care as usual.” The primary endpoints of the study will be the behavioural and psychological symptoms of dementia and the quality of life of people with severe dementia. The total duration of the study will be 18 months. Data will be collected by using observer rating scales. Discussion: The project has some outstanding quality features. The external validity is high, because it is situated in a naturalistic setting in nursing homes and is being carried out with available nursing employees. Due to this fact, a permanent implementation also seems to be possible. Since the participating nursing homes are disseminated across several German federal states and rural and urban regions, the results should be transferable to the entire population. Trial registration: ISRCTN15722923 (Registration date: 07 August 2019).
CRIS-Team Scopus Importer:2020-10-30
Keywords: Behavioural and psychological symptoms of dementia; Nursing home; Psychosocial intervention; Quality of life; RCT; Severe dementia

Under What Conditions Can People With Severe Dementia in Nursing Homes Benefit From a Multicomponent Psychosocial Intervention? - Diehl, Kristina; Kratzer, André; Grässel, Elmar (Gesundheitswesen, Supplement, 2023)
Background The majority of psychosocial interventions are considered effective in the treatment of dementia symptoms. However, there are hardly any evaluated concepts for people with severe dementia. An RCT study of patients with severe dementia in nursing homes during the Covid-19 pandemic found no effect of the newly developed multi-component intervention MAKS-s (motor, activities of daily living, cognitive, social version for persons with severe dementia) on patients quality of life, behavioural and psychological symptoms. Material and methods At the end of the controlled phase, 6 months after beginning of the study, the nursing staff of the control groups were also trained in MAKS-s. They were then free to decide whether and how often they wanted to use MAKS-s (open phase). By means of a written follow-up survey, conconducted with trained therapists, after another 6 months, predictors for positive effects of the intervention on people with severe dementia were to be identified. The survey also aimed to identify predictors of therapy fidelity. Data acquisition based on a self-developed questionnaire, assessing the therapists' subjective ratings of the three areas of structure, process and outcome quality of the MAKS-s intervention. Apart from descriptive evaluations, the predictors of benefit for people with severe dementia were analysed using a linear regression model and the predictors of therapy fidelity by using a binary logistic regression model. Results The more pronounced the normative restrictions due to the Covid-19 pandemic were, the more frequently manual deviations were observed. Fewer deviations from the manual were significantly associated with positive effects on people with severe dementia. Conclusion The results indicate the importance of therapy fidelity for the success of MAKS-s intervention. Therapy fidelity is decisive for the extent of the positive effects of MAKS-s, experienced by the therapists. Furthermore, the survey results show that activity-restricting pandemic policies in nursing homes negatively influenced the perceived effectiveness.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Covid-19; dementia; nursing homes; psychosocial intervention; Treatment adherence and compliance

Wenn es nicht mehr alleine geht – Inanspruchnahme ambulanter Unterstützungsangebote von Menschen mit Demenz: der Bayerische Demenz Survey (BayDem) - Karrer, Linda; Dietzel, Nikolas; Wolff, Franziska; Kratzer, André; Hess, Manuela; Grässel, Elmar; Kolominsky-Rabas, Peter (Gesundheitswesen, 2020)
Background The increasing prevalence of dementia raises challenges concerning the care of people with dementia (pwd). The care of pwd is mainly conducted by informal caregivers who are faced with several burdens; however, use of care services is generally low. The aim of this study was to identify predictors of the use of outpatient care services. Methods The Bavarian Dementia Survey (BayDem) is a multi-centre, longitudinal study that was conducted at 3 different sites in Bavaria, Germany. Participants were people with dementia (pwd) (according to ICD-10) and their informal caregivers. Data were collected by standardised face-to-face interviews using well-designed instruments in cooperation with local partners. Logistic regression analysis was carried out in order to identify predictors of the use of outpatient care services. Results In total, 364 pwd and 339 informal caregivers were included at the beginning of the study BayDem. The use of supportive care services was generally low. One-third of all participants used outpatient care services. In the logistic regression analysis, the following significant predictors for the use of outpatient care services 6 months after baseline were identified: severity of cognitive impairment of the pwd; use of outpatient care at the beginning of the study. Conclusion The low use of outpatient care services is a well-known paradoxical phenomenon. Such services can help give relief to informal caregivers. In order to enhance the use of supportive outpatient care services, there should be more focus on innovative health service delivery models with a low access threshold barrier. Besides more public campaigns, more guidance for existing offers is needed.
CRIS-Team Scopus Importer:2020-02-04
Keywords: informal caregivers; outpatient care; People with dementia; Resource Utilization in Dementia (RUD); use of care services

Zeitgerechte Diagnosestellung bei Menschen mit Demenz: der Bayerische Demenz Survey (BayDem) - Wolff, Franziska; Dietzel, Nikolas; Karrer, Linda; Kratzer, André; Hess, Manuela; Grässel, Elmar; Kolominsky-Rabas, Peter (Gesundheitswesen, 2020)
Background In many cases, people with dementia (PWD) receive their first diagnosis at an advanced stage of the disease. A timely diagnosis, however, is crucial for the utilization of therapies and support services for PWD and their caregivers. So far, only a few international studies have analysed predictors of the time lapse between the first perceived symptoms and diagnosis. The aim of this study was to assess the time span from the first symptoms of dementia until the first dementia diagnosis and to identify predictors of a timely diagnosis. Methods The Bavarian Dementia Survey (BayDem) is a multi-centre, longitudinal study at 3 different sites in Bavaria, Germany. Participants were PWD as defined by ICD-10 and their informal caregivers. Data was collected by standardized face-to-face interviews in cooperation with local actors. For the analysis of potential sociodemographic predictors of a timely diagnosis within 9 months after the perception of the first symptoms, binary logistic regressions were used. Results The median length from the perception of the first symptoms until diagnosis was 16 months. Predictors of a timely diagnosis for male PWD were age at the time of the first perceived symptoms and education. There was no association between a timely diagnosis and the place of residence or living situation of the PWD. Conclusions Diagnosis of dementia is often made with a huge delay. Therefore, it is necessary to enhance structured access routes to a timely diagnosis in primary care.
CRIS-Team Scopus Importer:2020-02-04
Keywords: dementia; diagnostic delay; time to diagnosis; timely diagnosis